Progressive collapsing foot deformity treated by calcaneus osteotomy, flexor digitorum longus transfer, and peroneus brevis-to-longus tenodesis - Veiga Sanhudo, José Antonio; Marin Canuto, Giorgio (Journal of the Foot & Ankle, 2022)
Objective: This study presents the results of progressive collapsing foot deformity treatment with calcaneus osteotomy, flexor digitorum longus transfer, and peroneus brevis-to-longus transfer as an adjuvant in the correction of the deformity. Methods: The outcomes of 22 patients with posterior tibial tendon dysfunction who underwent calcaneal osteotomy and flexor digitorum longus transfer combined with peroneus brevis-to-longus transfer (tenodesis) were evaluated retrospectively. Results: According to the Visual Analog Scale, pain scores improved from a mean of 7.1 at baseline to 1.6 after a mean follow-up of 32 months. The mean AOFAS score was 45.3 points preoperatively and 86.3 points at follow-up. Comparison of preoperative and postoperative radiographic parameters was possible in 16 patients (73%), demonstrating significant improvements in Meary’s angle and calcaneal pitch. Conclusion: Based on these findings, we conclude that correction of progressive collapsing foot deformity through a combination of calcaneal osteotomy, flexor digitorum longus transfer, and peroneal tenodesis leads to improvement in clinical and radiographic parameters. Level of Evidence IV; Therapeutic Studies; Case Series.